Meningkatkan Kualitas Hidup Masyarakat Desa Celuk melalui Edukasi Herbal dan Senam Pencegahan Osteoporosis - Widowati, I Gusti Ayu Rai; Widhiantara, I Gede; Sutema, I.A Manik Partha; Maharianingsih, Ni Made; Manuaba, I.A Ratih Wulansari; Widiastini, Luh Putu; Widyanthari, Desak Made; Jawi, I Made (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2024)
Background: The Celuk - Sukawati Village tourist area is one of the favorite tourist attractions in Gianyar Regency. Most of the population work as silver and gold craftsmen. Even though the local community has relatively high income and education, empirically the community still maintains the tradition of using herbal medicine to prevent or treat disease, but they do not understand how to process it and do not understand the correct dosage. Community service activities are organized by Udayana University and Bali International University, to educate the community. Method: the method of implementing this activity includes several important stages, namely socialization of osteoporosis prevention exercises to maintain bone health; followed by education regarding herbal medicines regarding their types and benefits; and ended with a discussion and question and answer session to deepen participants' understanding. The activity closed with a demonstration on making herbal drinks, where participants could see the making process directly and taste the results, so they could practice it themselves at home. Result: This activity involved around 100 people from various age groups, who actively participated in the entire series of events. The activities ran smoothly and were supported by extraordinary attention and positive responses from the community. Conclusion: The target and output of this service program is to provide knowledge and insight to the community about how to make herbal drinks and improve physical health through exercise to prevent osteoporosis. The implementation of community service with various parties needs to be intensified to provide benefits to improve the level of public health.